DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DA ATIVIDADE ANTINOCICEPTIVA DE UMA FORMULAÇÃO TÓPICA SEMISSÓLIDA CONTENDO NANOCÁPSULAS DE MELOXICAM - Bochi, Loana Dal Carobo Sagrilo (2018)
Nonsteroidal anti-inflammatory-drugs (NSAIDs) are widely used in situations that require anti-inflammatory and / or analgesic activity, such as arthritic disorders, posttraumatic or acute musculoskeletal disorders. However, NSAIDs can trigger gastrointestinal toxicity when treated orally. This work aimed at developing and characterizing a topical semi-solid formulation containing meloxicam nanocapsulate, and assesses the physical-chemical stability and determines the period of validity. In addition, this study sought to evaluate the antinociceptive activity of the hydrofilic gel containing meloxicam nanocapsulate (HGNCM), by oral route, using the model of writhing induced by acetic acid in mice. Through the physical-chemical analysis, suspensions containing meloxicam nanocapsulate showed appropriate and satisfactory features for incorporation into semi-solid databases. Samples were stored at room temperature (25 ± 2 ° C) and oven (40 ± 2 ° C and 75 ± 5% RH) for 180 days and analyzed every 30 days regarding its physical-chemical, organoleptic, rheological characteristics and content of the drug. These parameters were compared with the formulations containing meloxicam in free (HGM). The average diameter of particles and pH of HGNCM remained stable during 180 days of analysis, at both temperatures, but the pH of the HGM was reduced significantly when stored in an oven. The zeta potential of HGNCM had its negative charge increased after 180 days of analysis, at both temperatures. The HGNCM remained organoleptic characteristics by a period of time much larger than the HGM. Both HGNCM and HGM presented as a flow and non-Newtonian pseudoplastic behavior. The viscosity values were reduced significantly during the experiment for both formulations stored in an oven. The rheological characteristics were more stable for HGNCM than HGM, during 180 days of analysis at both temperatures. The analysis of the content (%) of HGNCM indicated that the NC may be exerting a protective action against the drug, allowing the maintenance of content above 90% even for the formulations stored 180 days in emissions compared to HGM. The validity estimate was higher for the HGNCM, both at room temperature and an oven and presented an antinociceptive effect more pronounced and prolonged when compared with the HGM. Through the results, we can conclude that the incorporation of meloxicam nanocapsulate in a hydrogel formulation presented satisfactory physical-chemical characteristics and stability, representing technological feasibility for the pharmaceutical area.